Shout Because You're Free : The African American Ring Shout Tradition in Coastal Georgia - Rosenbaum, Art (Book collections on Project MUSE., 1998)
"The ring shout is the oldest known African American performance tradition survivng on the North American continent. Performed for the purpose of religious worship, this fusion of dance, song, and percussion survives today in the Boldon community of McIntosh County, Georgia."